ELECTRONIC APPARATUS INCLUDING LIDAR SYSTEM AND METHOD FOR CONTROLLING ELECTRONIC APPARATUS - YUN, Juhwan; JEON, Jina (2024)
An electronic device includes a light detection and ranging (LiDAR) system including an Rx sensor including autofocus pixels distributed among image pixels for sensing image information. The LiDAR system also includes a Tx light source configured to output a pulse laser. A processor calculates a distance between the LiDAR system and a subject using the autofocus pixels included in the Rx sensor and drives the Tx light source based on the distance. The processor adaptively determines the transmission power of the Tx light source based on the distance to the subject, and controls the Tx light source to output a pulse laser according to the transmission power.